2019
DOI: 10.1002/adtp.201900081
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel‐Loaded Iron Oxide Nanoparticles for Targeted Breast Cancer Therapy

Abstract: Paclitaxel (PTX) is a potent drug for treating advanced solid carcinomas; however, its clinical utility is limited by its poor water solubility. Despite the promise of using nanoparticles to deliver hydrophobic PTX, achieving sufficient drug loading while maintaining small particle size and stability in biological media remains a challenge. Here, a PTX nanoparticle (NP) formulation with small size and great stability is presented that targets breast cancer cells and enables controlled release of PTX. This NP f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…The hydrophobic paclitaxel and folic acid were coupled to a metallic core, and the PEG served as a hydrophilic outer layer. When compared to free paclitaxel, the NPs system delivered the drug at conditions that mimicked the acidic intracellular pH of breast cancer cells, and the folic conjugation resulted in higher NP absorption by target cells, which increased the cytotoxicity to target cells (Jeon et al., 2019 ). In another study, for colon target dual drug delivery, a chitosan/palladium nanocomposite was created.…”
Section: Mechanism Of Cancer-targetingmentioning
confidence: 99%
“…The hydrophobic paclitaxel and folic acid were coupled to a metallic core, and the PEG served as a hydrophilic outer layer. When compared to free paclitaxel, the NPs system delivered the drug at conditions that mimicked the acidic intracellular pH of breast cancer cells, and the folic conjugation resulted in higher NP absorption by target cells, which increased the cytotoxicity to target cells (Jeon et al., 2019 ). In another study, for colon target dual drug delivery, a chitosan/palladium nanocomposite was created.…”
Section: Mechanism Of Cancer-targetingmentioning
confidence: 99%
“…Breast cancer tumor cells can be treated using several approaches including hyperthermia, delivery of anticancer drugs, oligonucleotides and peptides, photothermal and photodynamic therapy. 116 Benign or malignant cells are more heat sensitive compared to normal cells. [117][118][119] Tissue warming through hyperthermia treatment using Fe 3 O 4 nanoparticle is one of the promising means to treat tumor and metastasis.…”
Section: Applications Of Metal Oxide Nanoparticle For Overcoming Mdr ...mentioning
confidence: 99%
“…In addition, Jeon et al and Augustin et al have demonstrated the potential of IO NPs conjugated with paclitaxel and doxorubicin (Dox) for the treatment of some cancer subtypes. Furthermore, the polymer matrix of the molecular coating layer of NPs can be used to load and deliver drugs (Augustin et al, 2016;Jeon et al, 2019). For instance, Liu et al incorporated cisplatin on TiO 2 NPs coated with hyaluronic acid (HA), a polysaccharide that acts not only as a stabilizing agent but the matrix for drug loading.…”
Section: Therapeutic Agentsmentioning
confidence: 99%